Oral health status among pregnant and nonpregnant women: a comparative study - Kafle, Shristi; Singh, Harender; Sharma, Basant (Journal of Chitwan Medical College, 2021)
Background: Physiological alterations manifesting during pregnancy may influence oral health of women by increasing the susceptibility to oral infections. This study was carried out to assess oral hygiene status, gingival status, periodontal status and treatment needs (TNs) among pregnant and nonpregnant women. Methods: A comparative cross-sectional study was conducted in patients attending Outpatient Department of Obstetrics and Gynaecology, Chitwan Medical College and Teaching Hospital, Bharatpur, Chitwan, Nepal from December 2020 to June 2021. A total of 102 pregnant (34 in each trimester) and 102 nonpregnant women of 15-49 years fulfilling all inclusion criteria were evaluated for oral health status by various indices including oral hygiene index-simplified (OHI-S), gingival index (GI), and community periodontal index and treatment needs (CPITN). Convenience sampling technique was done. Data was analysed in SPSS v.26.0. Results: The mean scores of OHI-S, GI and CPITN were statistically (p value<0.001) higher in pregnant women compared to nonpregnant women; highest in third trimester followed by second and first trimesters. In both groups, majority were found to have score 2 for treatment needs. TN2, encompassing oral hygiene instructions and oral prophylaxis was required by 92.2% of nonpregnant women, 100% of pregnant women in first trimester, 88.2% and 5.9 % in second and third trimesters respectively. Majority (94.1%) of pregnant women in third trimester required TN3 complex treatment. Conclusions: Pregnant women found to have poor oral hygiene status, more gingivitis and periodontal diseases as compared to nonpregnant women. Implementation of proper oral hygiene practices can prevent oral diseases and its further complications.